Evaluasi Penggunaan Program E Learning Menggunakan Model CIPP - Sri Arita; Rita Syofyan; Hendrik Heri Sandi; Nia Ariyani Erlin (Jurnal Ecogen, 2023)
The E-Learning program is able to make it easy for lecturers and students to continue learning even though they do not meet face to face. And this program is designed with various menus that can provide different colors in the implementation of the learning process. However, this must of course be supported by aspects related to supporting the success of a system, such as human resources, facilities and infrastructure, institutional policies, readiness of various supporting aspects and so on. The evaluation used uses the CIPP model (Context, Input, Process and Product. Based on literature studies and research publications, this model is proven to be able to explain the components of the E-Learning program and provide an overview of the use of the E-Learning program at Padang State University. This research will evaluate the E-Learning program at UNP using the CIPP model. In this research the model CIPP is used in evaluating the E-Learning context, input or input in the E-Learning program. Evaluation of the process of using E-Learning and evaluation of the results of the E-Learning program. This is very important to research considering the high use of E-Learning Programs in learning at the Universitas Negeri Padang. The method used in this research is a quantitative descriptive method, research which aims to explain existing phenomena by using numbers to explain the characteristics of individuals or groups